1974
DOI: 10.1139/v74-252
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of 2,4,6-Trinitrotoluene and 2,4,6-Trinitrotoluene-d3 with Sodium Isopropoxide in Isopropyl Alcohol

Abstract: The reaction of sodium isopropoxide with 2,4,6-trinitrotoluene (TNT) and TNT-d3 (deuterated methyl group) in isopropanol has been investigated using stopped-flow techniques. Two absorbing species, identified as a σ-complex and the TNT anion (TNT−) are formed in this reaction. The formation of TNT− involves a rate determining proton transfer as shown by the observation of an isotope effect[Formula: see text] A spectrum of the σ-complex was calculated from initial rate data and was observed experimentally at low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…AS0 reflect decreasing solvation of the resulting 1 : 1 o-complex (24). By analogy we might expect that of the three complexes under consideration here the cyanide ion -2,4,6-trinitroanisole complex is least strongly solvated by isopropanol.…”
mentioning
confidence: 90%
“…AS0 reflect decreasing solvation of the resulting 1 : 1 o-complex (24). By analogy we might expect that of the three complexes under consideration here the cyanide ion -2,4,6-trinitroanisole complex is least strongly solvated by isopropanol.…”
mentioning
confidence: 90%
“…The reaction of I ,1,3,3-tetramethylguanidine (TMG) with 2,4,6-trinitrotoluene (TNT) in dipolar aprotic solvents has been shown to be a proton transfer from the methyl group ( I , 2), and a number of primary deuterium kinetic isotope effects have been measured for the proton transfer reaction with various bases and solvents (3)(4)(5)(6)(7). Nevertheless, it has also been noted (3,6,7) that nucleophilic attack by some bases could take place on the benzene ring to yield a a-complex.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has also been noted (3,6,7) that nucleophilic attack by some bases could take place on the benzene ring to yield a a-complex. The ring attack took place at the 3 position instead of the I position as originally observed by Meisenheimer (8).…”
Section: Introductionmentioning
confidence: 99%
“…Hence it appeared that a unique theory for this phenomenon could not apply and several proposals evolved to account for its origin (vide infra). It occurred to us that structural modification could produce useful information and, while use of alkyl substituted nitroaromatics could be considered, study of 2,4,6-trinitrotoluene has shown that alkoxide ion can partake in proton abstraction to give a nitrobenzylic anion in addition to a-complex formation (16)(17)(18)(19). On the other hand, use of 1-phenyl-2,4,6-trinitrobenzene (4) would preclude proton abstraction from occurring, while providing a model to test the importance of steric and delocalization effects.…”
mentioning
confidence: 99%